Antibacterial Activity of Brown Macroalgae Lipid (Sargassum duplicatum) to The Methicillin Resistant Staphylococcus aureus (MRSA) And Shigella dysentriae Bacteria - Riong Seulina Panjaitan; Ani Rombe Sarungngu’; Lika Lastri Sitorus (Department of Chemical Education Faculty of Teacher Training and Education Universitas Su, 2020)
Methicillin Resistant Staphylococcus aureus (MRSA) is the main cause of nosocomial infections in burn patientsdue to the occurrence of antibiotic resistance. Dysentery or shigellosis is an infection that causes sores (ulcers) in the large intestine in the middle caused by the bacteria Shigella dysentriae. Some studies show that Sargassum duplicatum has antibacterial abilities. This study aimsto determine the antibacterial activity of Sargassum duplicatum seaweed lipid extract to the bacteria Methicillin Resistant Staphylococcus aureus (MRSA) and Shigella dysentriae bacteria. The method used in this study was the Folch method (using sochletation with a solvent ratio of chloroform:methanol (2:1)) to extract lipids from Sargassum duplicatum. Then using the paper disc diffusion method with positive control of tetracycline. From the extraction results obtained, the lipid levels of Sargassum duplicatum, where the chloroform phase was 0.493% (b / b) and the methanol phase was 2.40% (b / b). The results of the lipid antibacterial activity of Sargassum duplicatum at the pure concentration in the methanol phase with an average concentration of 7.07 mm on the Methicillin Resistant Staphylococcus aureus (MRSA) Bacteria while in the Shigella dysentriae bacteria obtained an average of 7.05 mm and the chloroform phase obtained an average diameter of 9.16 mm on Methicillin Resistant Staphylococcus aureus (MRSA) and in Shigella dysentriae Bacteria an average of 3.99 mm while tetracycline antibiotics amounted to 11.67 mm on Methicillin Resistant Staphylococcus aureus (MRSA) and 18.98 mm in Shigella dysentriae bacteria.